The Role of Social Support in the Relationship between Problematic Social Media Use and Psychological Well-Being in Young People: A Systematic Review - Wilhelmina, Thifal Maida; Pihasniwati, Pihasniwati (LPPM Universitas 17 Agustus 1945 Samarinda, 2025)
The high prevalence of social media usage in young people go hand in hand with various problems caused, one of which is the problematic social media use (PSMU). This study aims to explore the role of social support in the relationship between PSMU and psychological well-being in young people. The method used is systematic literature review using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines by tracing previous studies related to the research topic. Article searches were conducted through the databases of Pubmed, Sciencedirect, Taylor & Francis, and PsycNet databases with attention to specific inclusion and exclusion criteria. The results show that social support has a dual role as a mediator as well as a moderator in the relationship between PSMU and psychological well-being. PSMU was found to cause emotional impacts, including depression, anxiety, and psychological distress, as well as social impacts, including social isolation, and loneliness. These findings highlight the need for interventions that strengthen social support and for further research involving young people in Indonesia.